Latest trends and global challenges of the development of international economic relations - Iryna Ivashchuk (Cхід, 2013)
The article provides an outline of modern tendencies of international economic relations in the context of increasing openness of national economies and growing protectionism. It is offered to consider economic development of countries as changing the geopolitical map of the world under influence of globalization. The article defines the main tendencies of evolutionary development of countries and proves the inexpedience of applying development strategies of certain countries to the developing countries. It proves the necessity of reconsidering the world economic order and defines the historic role of globalization in its formation. It analyzes the main features of interpreting globalization as a socio-historic process. Based in this, it defines that globalization increases the level of economic cooperation between countries that was initiated in the middle of XX century, but the uncertainty in the development of contemporary international economic relations disrupts the functioning of world financial infrastructure and increases the threat to national sovereignty of countries. It is proved that restricting the independence of states in choosing their trajectories of development contradicts the documents of international organizations, namely the United Nations. The article also reviews the ideological ideas of mondalism and its relation to globalization, which allows for confirming the utopianism of the idea of formatting a holistic world and the impossibility of one-sided world construction. It estimates the scenarios of world economic relations development under the influence of globalization and proves that heterogeneity of global environment will remain until the structure of global economy changes as a result of a constructive dialogue.